The Selection Effect and the Inflation-Output Variability Trade-off - Engin Kara (Center for Economic Studies and ifo Institute (CESifo), 2015)
It has been shown that extending the Calvo model to account for the heterogeneity in price stickiness suggested by the micro-evidence significantly improves the performance of the model. In the new model, price-changing firms are chosen disproportionately from sectors with more flexible prices. In this paper, I show that this selection effect significantly affects policy conclusions that arise from the model. In the new model, the level and the variability of inflation is higher than in the Calvo model with no selection effect. Attempting to lower inflation's variability results in a significant increase output's variability, without changing inflation's variability much.
Keywords: E00; 330; DSGE models; selection effect; variance trade-off; Multiple Calvo; Calvo